Efecto de la combinación de alimento artificial y biomasa de artemia sp en cría intensiva de postlarvas de litopenaeus vannamei. - Ordoñez Mejia, Cristhian Alexander (Machala : Universidad Técnica de Machala, 2020)
The most cultivated shrimp species worldwide is Litopenaeus vannamei, this is due to its great adaptability to different environments. The increase in viral and bacterial diseases in shrimp farming has led to the use of a culture system with greater biosecurity and sustainability, which is why it has been chosen to reduce the exchange of water, achieving production in systems with zero or very low exchange. replacement. Raceways are intensive production systems used as nurseries in shrimp farming, where the main aim is to ensure the survival and health of the postlarvae; for which factors such as artificial and natural feeding, environmental factors and water quality intervene. One of the drawbacks of these intensive systems is the excessive nitrogen that enters the system, due to the fact that artificial foods are not totally consumed; food residues accompanied by shrimp excreta are converted into ammonia by microbial processes; This metabolite is toxic under conditions of pH and high temperatures, becoming a limitation for the intensive production of postlarvae. In this context, in the facilities of the Technical University of Machala in the Academic Unit of Agricultural Sciences, in the Mariculture Station located at coordinates 3 ° 17'31.2 "S 79 ° 54'50.3" W, belonging to the City of Machala, in the Province of El Oro, an experimental trial was carried out with the objective of evaluating the effect of the combination of artificial feed and Artemia sp biomass in the intensive rearing of Litopenaeus vannamei postlarvae, using weight gain as variables, the survival and the feed conversion factor in a time of 15 days. The population studied was 900 postlarvae, in PL-14 stage, with an average weight of 3.8 mg, distributed in 9 drawers with a volume of 30 L of seawater with a salinity of 28 UPS. The sowing density with which we worked was 10 PL L-1. The treatments consisted of 25 and 50% replacement of artificial feed with brine shrimp biomass and a control that consisted of 100% artificial feed. The artificial food used for feeding was a Microencapsulated food of 300 microns and 45% protein; The brine shrimp biomass used as replacement for the artificial feed was obtained from a culture of brine shrimp fed with microalgae of the Thalassiosira sp and Tetraselmis spp. species. The feeding was based on feeding tables for raceway and in the daily siphons, 8 feeding doses were added with a frequency of 3 hours. The average weight gain at the end of the experiment was for treatment 1 and 2 of 27.8 ± 4.8 mg and 27.2 ± 6.0 mg respectively where they did not present significant differences and for the control it was 40.36 ± 3.9 mg, it presented a significant difference in the ANOVA and the Tukey's test with a p value <0.05, this with respect to treatment 1 and 2. The average survival at the end of the experiment was for treatment 1 and 2 68.5 ± 4.95% and 50.66 ± 6.6% respectively and the control 32.0 ± 6.12 %, finding a statistically significant difference in treatment 1 with respect to treatment 2 and the control with a p value <0.05. The feed conversion factors were 1.55 (T1), 2.1 (T2) and 2.25 (Control). No significant differences were found, however, treatment 1 and 2 obtained lower values ​​compared to the control. The average dissolved oxygen concentration in the morning hours was 6.0 ± 0.3 ppm and an average of 5.5 ± 0.3 in the afternoon hours, the temperature presented an average value of 24.7 ± 0.8 ° C in the morning hours and 28.0 ± 0.2 ° C in the afternoon. It was concluded that there is a positive influence on the combination of artificial feed with brine shrimp biomass regarding the survival of Litopenaeus vannamei postlarvae.
La especie de camarón más cultivada a nivel mundial es el Litopenaeus vannamei, esto se debe a su gran adaptabilidad a diferentes ambientes. El aumento en enfermedades virales y bacterianas en el cultivo de camarón ha conducido a la utilización de sistema de cultivos con mayor bioseguridad y sustentabilidad por lo que se ha optado a la reducción del intercambio de agua, logrando producir en sistemas con cero recambio o muy bajo recambio. Los raceway son sistemas de producción intensiva utilizados como maternidades en el cultivo de camarón, en donde se trata de asegurar principalmente la supervivencia y la salud de las postlarvas; para lo cual intervienen factores como alimentación artificial y natural, factores ambientales y de calidad de agua. Uno de los inconvenientes de estos sistemas intensivos es el excesivo nitrógeno que ingresa al sistema, debido a que los alimentos artificiales no son totalmente consumidos; los residuos de alimento acompañados de las excretas del camarón son convertidos en amonio por procesos microbianos; este metabolito es tóxico en condiciones de pH y temperaturas elevadas, convirtiéndose en un limitante para la producción intensiva de postlarvas. En este contexto, en las instalaciones de la Universidad Técnica de Machala en la Unidad Académica de Ciencias Agropecuarias, en la Estación de Maricultura ubicada en las coordenadas 3°17'31.2"S 79°54'50.3"W, perteneciente a la Ciudad de Machala, en la Provincia de El Oro, se realizó un ensayo experimental con el objetivo de evaluar el efecto de la combinación de alimento artificial y biomasa de Artemia sp en la cría intensiva de postlarvas de Litopenaeus vannamei, poniendo como variables la ganancia de peso, la sobrevivencia y el factor de conversión alimenticio en un tiempo de 15 días. La población estudiada fue de 900 postlarvas, en estadio PL-14, con un peso promedio de 3.8 mg, distribuidos en 9 gavetas con un volumen de 30 L de agua de mar con una salinidad de 28 UPS. La densidad de siembra con la que se trabajó fue de 10 PL L-1. Los tratamientos consistieron en el 25 y 50% de reemplazo del alimento artificial por biomasa de artemia y un control que consistió en 100% alimento artificial. El alimento artificial utilizado para alimentación fue un alimento Microencapsulado de 300 micras y 45% de proteína; la biomasa de artemia utilizada como reemplazo del alimento artificial fue obtenida de un cultivo de artemia alimentada con microalgas de las especies Thalassiosira sp y Tetraselmis spp. La alimentación se basó en tablas de alimentación para raceway y en los sifones diarios, se adicionaron 8 dosis de alimentación con una frecuencia de 3 horas. La ganancia de peso promedio al final del experimento fue para el tratamiento 1 y 2 de 27.8 ± 4.8 mg y 27.2 ± 6.0 mg respectivamente donde no presentaron diferencias significativas y para el control fue de 40.36 ± 3.9 mg presentó diferencia significativa en el ANOVA y la prueba de Tukey con un valor p<0.05, esto con respecto al tratamiento 1 y 2. La supervivencia promedio al final del experimento fue para el tratamiento 1 y 2 el 68.5 ± 4.95 % y 50.66 ± 6.6% respectivamente y el control 32.0 ± 6.12%, encontrando diferencia estadísticamente significativa en el tratamiento 1 con respecto al tratamiento 2 y el control con un valor p<0.05. Los factores de conversión alimenticia fueron 1.55 (T1), 2.1 (T2) y 2.25 (Control) no se encontró diferencias significativas, sin embargo, el tratamiento 1 y 2 obtuvieron valores menores en comparación al control. La concentración de oxígeno disuelto promedio en horas de la mañana fue de 6.0 ± 0.3 ppm y un promedio de 5.5 ± 0.3 en horas de la tarde, la temperatura presentó un valor promedio de 24.7 ± 0.8 °C en horas de la mañana y 28.0 ± 0.2 °C en la tarde. Se concluyó que existe una influencia positiva en la combinación de alimento artificial con biomasa de artemia en lo que respecta a la sobrevivencia de postlarvas de Litopenaeus vannamei.
Keywords: POSTLARVA; MICROALGAS; ARTEMIA; ALIMENTO